INOVASI MATERIAL HANDLING PANAS UNTUK KESELAMATAN, KONSISTENSI PROSES, DAN NILAI B2B INDUSTRI KIMIA - Prita Prasetya; Mochamad Hasan Purnomo; Moh Haifan (Journal of Innovation Research and Knowledge, 2026)
The chemical industry requires safe, stable, and consistent production processes, particularly in hot material handling activities. Manual handling of heated powder materials in glass containers may expose operators to heat, physical workload, potential container breakage, and inconsistent pouring movements. These conditions can affect occupational safety and process consistency. This study aims to examine the innovation of an automated hot material handling system as a process solution to improve safety, standardization, and B2B value in the chemical industry. The research used a descriptive-conceptual case study approach through direct observation, technical document review, and workflow analysis of the automation system. The results demonstrate that integrating an industrial robot, gripper, hopper, conveyor, safety fence, control system, and controller can support a safer and more structured material handling process. The system reduces direct operator involvement in high-risk areas and helps standardize the sequence of picking, pouring, and returning containers. In addition to improving operational safety and process consistency, this innovation also strengthens the company’s B2B value by demonstrating reliability, process control, and commitment to safer production. The findings indicate that automated hot material handling can be an important process innovation for supporting safer, more consistent, and more competitive chemical manufacturing operations.